Georgia Architectural and Historic Properties Survey of Washington St., Rebecca, Turner County, Ga., March 1981 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Washington St., Rebecca, Turner County, Ga., March 1981. 1 story L-shaped clapboard house with gabled tin roof. Set on brick piers. Double hung sash windows with 6/6 lights. Turned spindle posts support surrounding hipped porch. Poor condition. Date of Construction: c. 1900. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Washington St., Rebecca, Turner County, Ga., March 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 54.6 MB (57,349,729 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Rebecca (Ga.); Turner County (Ga.)